2019
DOI: 10.1186/s40425-019-0778-7
|View full text |Cite|
|
Sign up to set email alerts
|

Immunostimulatory RNA leads to functional reprogramming of myeloid-derived suppressor cells in pancreatic cancer

Abstract: BackgroundThe tumor microenvironment (TME) combines features of regulatory cytokines and immune cell populations to evade the recognition by the immune system. Myeloid-derived suppressor cells (MDSC) comprise populations of immature myeloid cells in tumor-bearing hosts with a highly immunosuppressive capacity. We could previously identify RIG-I-like helicases (RLH) as targets for the immunotherapy of pancreatic cancer inducing immunogenic tumor cell death and type I interferons (IFN) as key mediators linking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…The traditional classification of myeloid cells in the periphery and MDSC at the tumor site have recently been revised using several modern technologies, aiming at categorizing single cells based on their gene signature (single-cell RNAseq) and expression of cell surface receptors and some intracellular proteins (mass cytometry, CyTOF). The basic hypothesis is that, beyond the variety between human and mouse in the classification of these cells (24), in each species, the gene signature and cell surface protein expression may vary depending on the organ from which cells are isolated (BM, spleen, blood, LNs, tumor site) and may also differ between tumor types (122)(123)(124)(125)(126). These studies are still in early development but may pave a new direction in scientific research and its translational implications.…”
Section: A Future View Of the Classical Two-stage Model In Light Of Mmentioning
confidence: 99%
“…The traditional classification of myeloid cells in the periphery and MDSC at the tumor site have recently been revised using several modern technologies, aiming at categorizing single cells based on their gene signature (single-cell RNAseq) and expression of cell surface receptors and some intracellular proteins (mass cytometry, CyTOF). The basic hypothesis is that, beyond the variety between human and mouse in the classification of these cells (24), in each species, the gene signature and cell surface protein expression may vary depending on the organ from which cells are isolated (BM, spleen, blood, LNs, tumor site) and may also differ between tumor types (122)(123)(124)(125)(126). These studies are still in early development but may pave a new direction in scientific research and its translational implications.…”
Section: A Future View Of the Classical Two-stage Model In Light Of Mmentioning
confidence: 99%
“…To study the role of IRF4 in pancreatic cancer we made use of a transplantable, orthotopic tumor model using the tumor cell line T110299, which originate from a genetically engineered, spontaneous mouse model with PDAC-characteristic driver mutations (Kras G12D Tp53 R172H ). We recently reported that this model is particularly enriched for myeloid cells such as MDSC [31]. Three weeks after orthotopic tumor induction, tumor weight of Irf4 −/− mice was significantly increased compared to IRF4 sufficient Irf4 flox/flox controls ( Fig.…”
Section: Systemic Irf4 Deficiency Accelerates Pdac Tumor Growth and Ementioning
confidence: 88%
“…Given the substantial reduction of intratumoral CD8 + T cells, it seems more likely that this is due to an impaired sustained activation of antitumoral T cells than due to the amplification and action of MDSC in IRF4-deficent mice. We recently demonstrated that in the PDAC model used the PMN-MDSC frequency correlates with tumor weight [ 31 ]. One can therefore argue that the elevated levels of PMN-MDSC in the global IRF4 deficient mouse could be a secondary effect of the increased tumor size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is context-dependent and is attributed to crosstalk with antigen-presenting cells (APCs), enhanced IL-6 activity and a suppressive Treg gene signature [143][144][145]. Pattern recognition receptor (PRR) signaling and type I IFN induction counteracts MDSC expansion and function [146,147]. Tumor cell-intrinsic type I IFN functions include the induction of tumor cell death, enhanced MHC class I expression and tumor antigen presentation [139][140][141][142].…”
Section: Type I Ifnsmentioning
confidence: 99%